2020
DOI: 10.1186/s12903-020-01223-2
|View full text |Cite
|
Sign up to set email alerts
|

Does the rate of orthodontic tooth movement change during pregnancy and lactation? A systematic review of the evidence from animal studies

Abstract: Background: The changes in bone homeostasis observed during pregnancy and lactation could result in alterations in the rate of orthodontic tooth movement, but research in human subjects presents significant ethical and practical limitations. Our aim was to compare the amount of orthodontic tooth movement between pregnant/ lactating or not animals. Methods: We searched without restrictions 8 databases and performed hand searching until July 2019 (PubMed, Central, Cochrane Database of Systematic Reviews, SCOPUS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 66 publications
0
6
0
3
Order By: Relevance
“…A great number of studies emphasized on tooth movement acceleration as well as how to measure it. [ 82 83 ] Several techniques have been used to accelerate tooth movement, such as biological approaches (e.g., cytokines, prostaglandin, or parathyroid hormone injection), device-assisted techniques, surgical methods (e.g., corticotomy, interseptal alveolar surgery, osteotomy), and LLLT. [ 82 ] Although surgical techniques have been proved to enhance tooth movement acceleration,[ 84 ] it could be considered more aggressive than other methods.…”
Section: Discussionmentioning
confidence: 99%
“…A great number of studies emphasized on tooth movement acceleration as well as how to measure it. [ 82 83 ] Several techniques have been used to accelerate tooth movement, such as biological approaches (e.g., cytokines, prostaglandin, or parathyroid hormone injection), device-assisted techniques, surgical methods (e.g., corticotomy, interseptal alveolar surgery, osteotomy), and LLLT. [ 82 ] Although surgical techniques have been proved to enhance tooth movement acceleration,[ 84 ] it could be considered more aggressive than other methods.…”
Section: Discussionmentioning
confidence: 99%
“…El estrógeno aumenta en gran manera en las etapas del embarazo, y este es esencial para la preservación de la masa ósea en el embarazo, pero la deficiencia de estrógeno puede afectar a las células osteoblásticas contribuyendo a la pérdida ósea durante la lactancia. Por lo tanto si los minerales de la madre no son suficientes y escasos, se extraerá de sus fuentes esqueléticas maternas, que puede afectar su estructura esquelética y masa ósea 1 .…”
Section: Movimientos Dentarios En Mujeres Embarazadas Y Su Relación C...unclassified
“…En cuanto al movimiento dentario ortodóntico durante el embarazo y la lactancia posiblemente exista alteraciones en el movimiento de los dientes, esto debido a los cambios de homeostasis ósea, las alteraciones de resorción dentaria y la deposición ósea observada en el embarazo. Sin embargo, esta información aún no se ha resumido de una manera basada en la evidencia dado que para hacerlo en seres humanos presenta importantes limitaciones éticas y prácticas, solo el uso de animales nos puede proporcionar un medio de comprensión 1 .…”
Section: Movimientos Dentarios En Mujeres Embarazadas Y Su Relación C...unclassified
See 1 more Smart Citation
“…Orthodontic tooth movement involves intracellular pathways, intercellular physiological signaling processes, as well as interactions between cells and the extracellular environment that are regulated by hormones, growth factors and cytokines [ 4 ]. Information from studies conducted in female experimental animals have suggested that bone metabolism alterations occurring during pregnancy and lactation, as well as the osteoporotic changes following ovariectomy, may have an impact on the rate of tooth movement [ 5 , 6 ]. Furthermore, it could be hypothesized that the endocrine controls that govern the menstrual cycle may influence bone resorption and apposition under the effect of orthodontic forces as well.…”
Section: Introductionmentioning
confidence: 99%